Entrepreneurship by necessity a factor that affects youth unemployment in students of the Business Science Faculty, 2015 - Catacora Lira, Luis Celerino (2015)
Objective: The research's main objective was to determine the incidence of unemployment by necessity in the initiation and development of entrepreneurship in students from the School of Business Administration in 2015. Method: For the development of the study, was appropriate to apply for the design of explanatory descriptive, not experimental. The study sample consisted of students of the V and VII cycle of the Professional School of Business Administration School of Business. Two questionnaires designed to collect information from each of the variables respectively prepared validated. The data were processed using the SPSS statistical program, and statistical analysis are descriptive and inferential. Result: The problem of unemployment is a concern for all governments seeks to solve. Youth unemployment is currently one of the issues that require treatment because they were on the rise and affects a significant number of young people. In that sense this research paper provides an explanation of the causes of the emergence and growth of youth unemployment. The issue transcends the classical thought that argues that youth unemployment is a result of the low investment made by companies in the economy. Because research has allowed to modify the thesis, and now argue that youth unemployment is the result largely of corporate improvisation and basic ignorance of economic theory by young people who rush first to market with a venture. Conclusions: In this context the present study was determined that entrepreneurship by necessity, has an impact on the emergence and growth of youth unemployment in the region of Tacna. Log enterprises in competitive economies and unpredictable markets, business require preparation, at least in substance; It is neither feasible nor advisable intending to start a business with the sole purpose to try their luck. It currently requires a lot of knowledge and economic, financial and commercial training